1986
DOI: 10.1159/000132265
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of leukocyte interferon gene in the pig (<i>Sus scrofa domestic</i><i>a</i> L.) by in situ hybridization

Abstract: Using as a probe pig genomic DNA, including the complete interferon α gene, we have mapped the leukocyte interferon gene on pig chromosome 1 by in situ hybridization. A total of 196 silver grains were noted on the 106 metaphases scored: 31% of the grains were observed on chromosome 1, and 67% of these were localized in the region 1q2.2→q2.7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

1989
1989
1997
1997

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…This observation confirms the one given by Lin et al 1985. We have also modified the washings after hybridization. They are less stringent and, in consequence, we have retained signal possibly lost in the first experiments (Yerle et al, 1986).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This observation confirms the one given by Lin et al 1985. We have also modified the washings after hybridization. They are less stringent and, in consequence, we have retained signal possibly lost in the first experiments (Yerle et al, 1986).…”
Section: Resultsmentioning
confidence: 91%
“…In 1986, we mapped the leukocyte interferon gene on pig chromosome 1 by in situ hybridization (Yerle et al 1986). The labeled region (q2.2 -q2.7) appeared to be large, considering that the probe used, contained only one alpha interferon gene.…”
Section: Introductionmentioning
confidence: 99%
“…1982) and glucose-regulated protein (78 kD) (GRP78) (Law et al. 1984) on chromosome 9. in the pig genome, both IFNA1 (Yerle et al, 1986) and GRP78 (Mcllink el al., 1992) reside on chromosome I. Our present results, taken together with pre vious mapping data, demonstrate that these three genes are syntenic in swine, as they arc in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we showed that, as in the human, bovine and equine species (Capon et al, 1985;Hauptmann & Swetly, 1985;Velan et al, 1985;Himmler et al, 1986), the porcine IFN-~ (PoIFN-~) multigene family can be divided into two homologous, but distinct classes of genes. The class I subfamily, located on porcine chromosome 1 (Yerle et al, 1986) contains at least 11 loci, of which nine have been cloned and two sequenced: PoIFN-~I and PoIFN-~2 (Lef6vre & La Bonnardi6re, 1986;F. Lef+vre, unpublished results).…”
Section: Introductionmentioning
confidence: 99%